Employment and exchange rates: the role of openness and technology - Fernando Alexandre; Pedro Baç\~ao; Jo\~ao Cerejeira; Miguel Portela (Institute for the Study of Labor (IZA), 2009)
Real exchange rate movements are important drivers of the reallocation of resources between sectors of the economy. Economic theory suggests that the impact of exchange rates should vary with the degree of exposure to international competition and with the technology level. This paper contributes by bringing together these two views, both theoretically and empirically. We show that both the degree of openness and the technology level mediate the impact of exchange rate movements on labour market developments. According to our estimations, whereas employment in high-technology sectors seems to be relatively immune to changes in real exchange rates, these appear to have sizable and significant effects on highly open low-technology sectors. The analysis of job flows suggests that the impact of exchange rates on these sectors occurs through employment destruction.
urn:nbn:de:101:1-2009061553
Keywords: J23; F16; F41; 330; Exchange rates; international trade; job flows; Kaufkraftparität; Internationaler Wettbewerb; Technologie; Arbeitsmobilität; Beschäftigungseffekt; Hochtechnologiesektor; Low-Tech; Theorie; Portugal